The Influence of Student Characteristics, Design Learning Features, and Learning Outcomes on Blended Learning Effectiveness (Case study: Higher Education in Indonesia) - Aditya Permadi; Bayu R Aditya (Edunesia: Jurnal Ilmiah Pendidikan, 2021)
Abstract: The purpose of this study is to determine the effect of student characteristics, design learning features, and learning outcomes on the effectiveness of blended learning. This research was conducted at a higher education institution in the city of Bandung, Indonesia. 376 The sampling method used was purposive sampling technique, in this case involving 376 students. The data analysis method used in this study was a multiple linear regression analysis. The findings of this study indicate that the design learning features and the learning outcomes can significantly influence the implementation of blended learning, while the student characteristics do not significantly influence. It shows that to increase the effectiveness of the implementation of blended learning, we need to maximize the design learning features. Besides, factors related to student motivation and satisfaction must also be considered. Thus, the effectiveness of implementing blended learning can be increased. Abstrak: Tujuan penelitian ini adalah untuk mengetahui pengaruh karakteristik siswa, desain fitur pembelajaran, dan hasil belajar terhadap keefektifan blended learning. Penelitian ini dilakukan di sebuah institusi pendidikan tinggi di kota Bandung, Indonesia. pengambilan 376 sampel yang digunakan dengan  teknik purposive sampling, dalam hal ini melibatkan 376 mahasiswa. Metode analisis data yang digunakan dalam penelitian ini adalah analisis regresi linier berganda. Temuan penelitian ini menunjukkan bahwa desain fitur pembelajaran dan hasil belajar berpengaruh signifikan terhadap penerapan blended learning, sedangkan karakteristik siswa tidak berpengaruh signifikan. Hal tersebut menunjukkan bahwa untuk meningkatkan keefektifan penerapan blended learning di pendidikan tinggi perlu memaksimalkan desain fitur pembelajaran. Selain itu faktor yang berhubungan dengan motivasi dan kepuasan mahasiswa juga harus diperhatikan. Dengan demikian efektivitas penerapan blended learning dapat ditingkatkan.